Factors Influencing the Dysmenorrhea among Korean Adolescents in Middle School - Jeon, Ga Eul (The Society of Physical Therapy Science, 2014)
[Purpose] This study aimed to examine the factors influencing dysmenorrhea among Korean middle school adolescents. [Subjects] The subjects included 572 female students in three different middle schools located in Seoul, South Korea. [Methods] A cross-sectional design was adopted. The measurement tools used included a demographic form and revised Menstrual distress Questionnaire (MDQ). [Results] The analyses showed that the prediction model was significant. The value of the adjusted R(2) was 0.282, which corresponds to an explanatory power of 28.2%. The factor found to have the most influence on dysmenorrhea among Korean middle school adolescents was stress, followed by health status, onset of dysmenorrhea, consecutive days of menstruation, and dietary habits. [Conclusion] Nursing intervention programs for alleviating dysmenorrhea in Korean middle school adolescents are essential in order to reduce their level of stress, improve their perceived health status, and help them to maintain regular dietary habits. Reflecting on the recent trend of female students menstruating at a younger age, public health education courses and counseling programs should offer customized methods for alleviating dysmenorrhea.